FUNGSI DAN TUGAS LEMBAGA PEMASYARAKATAN DALAM MELAKUKAN PEMBINAAN TERHADAP NARAPIDANA DI LEMBAGA PEMASYARAKATAN TANJUNG GUSTA KELAS I MEDAN - Ica Karina (LPPM Universitas Katolik Santo Thomas Medan, 2025)
Correctional Institutions are a development system that uses an approach that focuses on the potentials of prisoners and the community, so that the community is involved in developing and integrating prisoners into the community and is called the